2
$\begingroup$

I'm rusty on logarithms. What is the approach to a problem like this? Any hints would be appreciated.

I'm thinking the subtraction on the numerator and denominator can become division since the bases are the same?

enter image description here

$\endgroup$
  • $\begingroup$ Use $a \log_b m = \log_b m^a$ and $\log_b a - \log_b c =\log_b \frac ac$ to get that this is $\frac {\log_2\frac{24}{\sqrt {72}}}{\log_3 \frac {18}{\sqrt[3]{72}}}$. $\endgroup$ – fleablood Jan 18 at 22:17
5
$\begingroup$

The identities $\log_a b + \log_a c \equiv \log_a(bc)$ and $b\log_a c \equiv \log_a c^b$ will be needed here. You can then do \begin{align*} \frac{\log_2 24 - \frac 12 \log_2 72} {\log_3 18 - \frac 13 \log_3 72} &= \frac{\log_2 24 - \log_2 \sqrt{72}} {\log_3 18 - \log_3 \sqrt[3]{72}} \\ &= \frac{\log_2 \frac{24}{\sqrt{72}}} {\log_3 \frac{18}{\sqrt[3]{72}}} \\ &= \frac{\log_2 \frac{24}{3\sqrt 8}} {\log_3 \frac{18}{2\sqrt[3]{9}}} \\ &= \frac{\log_2 \frac{8}{\sqrt 8}} {\log_3 \frac{9}{\sqrt[3]{9}}} \\ &= \frac{\log_2 8 - \log_2 \sqrt 8} {\log_3 9 - \log_3 \sqrt[3]{9}} \\ &= \frac{\log_2 2^3 - \log_2 2^{3/2}} {\log_3 3^2 - \log_3 3^{2/3}} \\ &= \frac{3 - \frac 32} {2 - \frac 23} \quad \text{by definition} \\ &= \frac 98 \end{align*}

$\endgroup$
  • 1
    $\begingroup$ thank you for the detailed explanation! I am a little stuck on this: how does log(2)(8/sqrt(8)) become 3- 3/2? $\endgroup$ – PineNuts0 Jan 18 at 19:01
  • 1
    $\begingroup$ @PineNuts0 Sorry about that, I was a bit lazy and skipped a few steps. I have edited my answer somewhat, though let me know if it's still not clear enough about how you get the fractional exponents $\endgroup$ – Izaak van Dongen Jan 18 at 19:04
  • 1
    $\begingroup$ this is perfect ... thank you so much for taking time to spell out step by step. may I ask what software you use to type out the math? $\endgroup$ – PineNuts0 Jan 18 at 19:13
  • $\begingroup$ @PineNuts0 you're welcome :D. The way we type maths here is by directly entering LaTeX source. See this post for some more info. LaTeX is a very popular way to typeset maths, and well worth learning if you like your digital maths to look pretty. $\endgroup$ – Izaak van Dongen Jan 18 at 19:14
1
$\begingroup$

1)

$\log_2 24 =\log_2 (3\times 2^3)= \log_2 3 + \log_2 2^3 = \log_2 3 + 3$.

$\frac 12\log_2 72 = \frac 12 (\log_2 3^2\times 2^3) = \frac 12(\log_2 3^2 + \log_2 2^3)=\frac 12(2\log 3 + 3) = \log 3 +\frac 32$

So $\log_2 24 -\frac 12\log_2 72 = (\log_2 3 + 3)-(\log_2 3 +\frac 32) = \frac 32$

Likewise.

$\log_3 18 = \log_3 2\times 3^2 = \log_3 2 + \log_3 3^2 = \log_3 2 + 2$

$\frac 13\log_3 72 = \frac 13(\log_3 3^2\times 2^3) = \frac 13(\log_3 3^2 + \log_3 2^3)=\frac 13(2 + 3\log_3 2)= \frac 23+ \log_3 2$.

So $\log_3 18-\frac 12\log_3 72 = (\log_3 2+2)-(\frac 23 + \log_3 2)= \frac 43$.

So $\frac {\log_2 24 -\frac 12\log_2 72}{\log_3 18-\frac 13\log_3 72}=\frac {\frac 32}{\frac 43}=\frac 32\frac 34=\frac {9}8$.

2)

$\frac {\log_2 24 -\frac 12\log_2 72}{\log_3 18-\frac 13\log_3 72}=$

$\frac {\log_2 24 -\log_2 72^{\frac 12}}{\log_3 18-\log_3 72^{\frac 13}}=$

$\frac {\log_2 \frac {24}{72^{\frac 12}}}{\log_3 \frac {18}{72^{\frac 13}}}=$

$\frac {\log_2 \frac {3*2^3}{3^{2*\frac 12}2^{3*\frac 12}}} {\log_3 \frac{2*3^2}{3^{2*\frac 13}2^{3*\frac 13}}}=$

$\frac {\log_2 2^{\frac 32}}{\log_3 3^{\frac 43}}=$

$\frac {\frac 32}{\frac 43}=\frac 32\frac 34=\frac 98$.

$\endgroup$
1
$\begingroup$

Often better to factor the arguments of the logarithms to get to much simpler logarithms more quickly... \begin{align*} &\frac{\log_2 24 - \frac{1}{2} \log_2 72}{\log_3 18 - \frac{1}{3} \log_3 72} \\ &\quad{}= \frac{\log_2 (2^3 \cdot 3) - \frac{1}{2} \log_2 (2^3 \cdot 3^2)}{\log_3(2\cdot 3^2) - \frac{1}{3} \log_3 (2^3 \cdot 3^2)} \\ &\quad{}= \frac{\log_2 2^3 + \log_2 3 - \frac{1}{2} \left( \log_2 2^3 + \log_2 3^2 \right)}{\log_3 2 + \log_3 3^2 - \frac{1}{3} \left( \log_3 2^3 + \log_3 3^2 \right)} \\ &\quad{}= \frac{3\log_2 2 + \log_2 3 - \frac{1}{2} \left( 3\log_2 2 + 2\log_2 3 \right)}{\log_3 2 + 2\log_3 3 - \frac{1}{3} \left( 3\log_3 2 + 2\log_3 3 \right)} \\ &\quad{}= \frac{3 + \log_2 3 - \frac{1}{2} \left( 3 + 2\log_2 3 \right)}{\log_3 2 + 2 - \frac{1}{3} \left( 3\log_3 2 + 2 \right)} \\ &\quad{}= \frac{3 + \log_2 3 - \frac{3}{2} - \log_2 3 }{\log_3 2 + 2 - \log_3 2 - \frac{2}{3}} \\ &\quad{}= \frac{3 - \frac{3}{2}}{2 - \frac{2}{3}} \cdot \frac{6}{6} \\ &\quad{}= \frac{18-9}{12-4} \\ &\quad{}= \frac{9}{8} \text{.} \end{align*}

$\endgroup$
0
$\begingroup$

Rule 1: $\ \log_a(x^q) = q\log_a(x)$

Rule 2 (Addition): $\ \log_a(x) + \log_a(y) = \log_a(xy), \ $

Rule 3 (Subtraction): $\ \log_a(x) - \log_a(y) = \log_a(\frac{x}{y}), \ $

Rule 3 is actually Rule 2 but replacing y with $\ \frac{1}{y} =y^{-1}$, and then using Rule 1.

Rule 4 (Change of base): $\ \frac{\log_a(x^p)}{\log_a(x^q)} = \log_q(p)$

$\endgroup$
0
$\begingroup$

Yes, the subtractions can become division, and the fractions can become roots, plus $\log_a b =\frac 1 {\log_b a}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for?Browse other questions tagged or ask your own question.